(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Water quality is a critical concern for human well-being and ecological stability, particularly as groundwater serves as a vital source of freshwater globally, sustaining various societal sectors. Human activities have increasingly polluted groundwater with contaminants, notably heavy metals, presenting potential health hazards to communities reliant on these water sources. This study investigates heavy metal contamination in borehole water samples from four distinct locations within Giwo, Bauchi State, Nigeria, and evaluates the associated long-term health risks of consuming this water. Analysis of the water samples identified iron to have the highest concentration (1.140 mg/L) while lead recorded the lowest concentration (0.0003 mg/L), the concentrations of zinc and copper across all the four locations were within the Nigerian Standard for Drinking Water Quality (NSDWQ) established by the Nigerian Industrial Standard (NIS) of 3.0 mg/L and 1.0 mg/L. The Average Daily Intake (ADI) from water consumption for, zinc, iron, copper, cadmium, and manganese were consistently below their corresponding Reference Doses (RfDs) of 0.3 mg/kg/day, 0.7 mg/kg/day, 0.04 mg/kg/day, 0.0005 mg/kg/day, and 0.14 mg/kg/day, respectively for all water samples analyzed while the remaining heavy metals exhibited ADIs exceeding their established RfDs. Hazard Quotient (HQ) values for most metals were below the threshold of 1, suggesting a relatively low risk of adverse health effects. However, prolonged consumption of this water may heighten cumulative health risks associated with specific heavy metals, warranting continuous monitoring and remedial actions.